Closed Compression Nailing Using a New-Generation Intramedullary Nail without Autologous Bone Grafting for Humeral Shaft Nonunion - Genta Fukumoto; Tomoaki Fukui; Keisuke Oe; Atsuyuki Inui; Yutaka Mifune; Ryosuke Kuroda; Takahiro Niikura (Case Reports in Orthopedics)
Introduction. Although the recommended treatment for humeral shaft nonunion is compression plating with autologous bone grafting, we treated a case of humeral shaft nonunion with an intramedullary nail (IMN) without bone grafting. Presentation of Case. Osteosynthesis with IMN was performed on a 24-year-old man with a humeral shaft fracture at another hospital. However, bony union was not obtained 1 year after the first surgery, and he was referred to our institution. We treated the nonunion with exchange nailing without autologous bone grafting using compression function of the nail, leading to bony union at 7 months postoperatively. At the final follow-up 2 years and 4 months postoperatively, the patient had full range of motion in the left shoulder and elbow joints. Discussion. Compression plating with autologous bone grafting is reported to be the gold standard for the treatment of humeral shaft nonunion. IMN is advantageous for minimal invasion; however, the conventional type of IMN cannot apply compression force between fragments and does not have sufficient stability against rotational force. In this case, we used an IMN that could apply compression between the fragments and which had rotational stability via many screws. We did not perform bone grafting because the current nonunion was adjudged to be biologically active, and we achieved good functional results. Conclusion. We treated humeral shaft nonunion using IMN with compression, but without bone grafting, leading to successful clinical outcomes. This strategy might be an appropriate choice for the treatment of humeral shaft nonunion with biological activity.